Synthetic biology in the UK – An outline of plans and progress - Clarke,LJ; Kitney,RI (Synthetic and Systems Biotechnology, 2016)
Synthetic biology is capable of delivering new solutions to key challenges spanning the bioeconomy, both nationally and internationally. Recognising this significant potential and the associated need to facilitate its translation and commercialisation the UK government commissioned the production of a national Synthetic Biology Roadmap in 2011, and subsequently provided crucial support to assist its implementation.Critical infrastructural investments have been made, and important strides made towards the development of an effectively connected community of practitioners and interest groups. A number of Synthetic Biology Research Centres, DNA Synthesis Foundries, a Centre for Doctoral Training, and an Innovation Knowledge Centre have been established, creating a nationally distributed and integrated network of complementary facilities and expertise.The UK Synthetic Biology Leadership Council published a UK Synthetic Biology Strategic Plan in 2016, increasing focus on the processes of translation and commercialisation. Over 50 start-ups, SMEs and larger companies are actively engaged in synthetic biology in the UK, and inward investments are starting to flow.Together these initiatives provide an important foundation for stimulating innovation, actively contributing to international research and development partnerships, and helping deliver useful benefits from synthetic biology in response to local and global needs and challenges.